2022
DOI: 10.3389/fneur.2022.951536
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on astrocyte autophagy in ischemic stroke

Abstract: Ischemic stroke is a highly disabling and potentially fatal disease. After ischemic stroke, autophagy plays a key regulatory role as an intracellular catabolic pathway for misfolded proteins and damaged organelles. Mounting evidence indicates that astrocytes are strongly linked to the occurrence and development of cerebral ischemia. In recent years, great progress has been made in the investigation of astrocyte autophagy during ischemic stroke. This article summarizes the roles and potential mechanisms of astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 142 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…The rat cerebral cortex astrocytes were exposed to peroxide to form an oxidative stress model. After 2 hours of propofol treatment, it was found that the Glu release was significantly lower than that of the untreated group ( 14 , 20 ). Therefore, the combination of O 3 and propofol in this study has a better protective effect on stroke.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The rat cerebral cortex astrocytes were exposed to peroxide to form an oxidative stress model. After 2 hours of propofol treatment, it was found that the Glu release was significantly lower than that of the untreated group ( 14 , 20 ). Therefore, the combination of O 3 and propofol in this study has a better protective effect on stroke.…”
Section: Discussionmentioning
confidence: 82%
“…A study ( 14 ) has reported that autophagy in astrocytes induces the activation of astrocytes, which is common after stroke and causes brain damage. Thus, we speculated that the effect of O 3 in alleviating brain damage might be related to the autophagy of astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes and neurons exhibit varying degrees of autophagy under hypoxic-ischemic conditions, which may be linked to differences in the mechanisms that activate autophagy. [42]…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is regulated through the posttranslational modification of ATG proteins, encompassing processes such as phosphorylation, ubiquitination, acetylation, O-GlcNAcylation, N6-methyladenosine modification, oxidation, and cleavage. These modifications serve as indicators that can be monitored to assess the status of the autophagic process [202][203][204][205][206][207][208]. There are many methods for monitoring autophagy, including transmission electron microscopy (TEM), Western blot, immunofluorescence, flow cytometry, northern blot, reverse transcriptase polymerase chain reaction (RT-PCR), luciferase release assay, transgenic mice, and gene knockdown, to identify and quantify the status of autophagic flux in different pathological conditions.…”
Section: Future Research Avenues Monitoring Methods and Unresolved Qu...mentioning
confidence: 99%